2008
DOI: 10.1038/ncb1808
|View full text |Cite
|
Sign up to set email alerts
|

Amoeboid T lymphocytes require the septin cytoskeleton for cortical integrity and persistent motility

Abstract: The systems that refine actomyosin forces during motility remain poorly understood. Septins assemble on the T cell cortex and are enriched at the mid-zone in filaments. Septin knockdown causes membrane blebbing, excess leading edge protrusions, and lengthening of the trailingedge uropod. The associated loss of rigidity permits motility, but cells become uncoordinated and poorly persistent. This also relieves a previously unrecognized restriction to migration through small pores. Pharmacologically rigidifying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
216
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(235 citation statements)
references
References 37 publications
18
216
1
Order By: Relevance
“…As previously described (Kremer et al, 2005;Tooley et al, 2009;Sellin et al, 2011), efficient knockdown of SEPT7 resulted in the concomitant loss of the other two members of the complex, SEPT2 and SEPT9. Under these conditions, ciliogenesis was inhibited in ,50% of cells, and the primary cilia in the remaining ,50% of cells were significantly shorter than in the control.…”
Section: Discussionsupporting
confidence: 55%
“…As previously described (Kremer et al, 2005;Tooley et al, 2009;Sellin et al, 2011), efficient knockdown of SEPT7 resulted in the concomitant loss of the other two members of the complex, SEPT2 and SEPT9. Under these conditions, ciliogenesis was inhibited in ,50% of cells, and the primary cilia in the remaining ,50% of cells were significantly shorter than in the control.…”
Section: Discussionsupporting
confidence: 55%
“…This is not unexpected in light of a recent genome-wide screen for regulators of Ca 2+ signaling and nuclear factor of activated T-cells (NFAT) activation that identified septins as important modulators of store-operated Ca 2+ release, a pathway important for T-cell development and activation (Sharma et al, 2013;Fracchia et al, 2013). Moreover, septins are crucial for the maintenance of membrane dynamics, cell shape and motility in lymphocytes (Tooley et al, 2009;Gilden et al, 2012). Although septins play an important part in immune cell functions that are independent of cell division (summarized in Fig.…”
Section: Non-canonical Functions Of Septins In Immune Cellsmentioning
confidence: 94%
“…The first report addressing the requirement of septins in hematopoietic cell division came a year later. Interestingly, Krummel and co-workers analyzed the role of septins in the amoeboid migration of the murine T-lymphocytic D10.G4 cell line and observed that septin depletion had no effect on the proliferation of these cells (Tooley et al, 2009). This was followed by similar reports of septin-independent survival and proliferation of the human myeloid K562 cell line and of human T-lymphoblast jurkat cells (Sellin et al, 2011a).…”
Section: Functions Of Septins In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, septin assembly is restricted both in time and in space through local activation of small GTPases such as Cdc42. Localized signaling leads to higher-order septin structures forming closely apposed to the plasma membrane at the plane of division, sites of polarity, and curved membranes (10,(12)(13)(14). Notably, eukaryotic cells of different geometries build higher-order septin assemblies of various shapes, sizes, and functions (4, 15, 16).…”
mentioning
confidence: 99%